Aktivitas Ekstrak Metanol Bawang Putih (Allium sativum) sebagai Penghambat Pembentukan Biofilm pada Pseudomonas aeruginosa (The Activity of Methanolic Extract of Garlic (Allium sativum) in Inhibiting Growth of Biofilm in Pseudomonas aeruginosa) - Risty Pradana Linggan Wangi; Enny Suswati; Desie Dwi Wisudanti (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Garlic (Allium sativum) is one of the most important agricultural product that has organosulphur compound, such as alliin, allicin, and ajoene. Those organosulphur compound used as antibiofilm agent by inhibiting adhesion and quorum sensing process in Pseudomonas aeruginosa. The purpose of study was to identify the antibiofilm effect and Minimum Biofilm Inhibitory Concentration (MBIC) of methanolic extract of garlic against the growth of P. aeruginosa biofilm. This was quasi experimental with posttest only control group design. The colony of P. aeruginosa were divided into 7 groups with 5 groups used methanolic extract of garlic as P1-P5 at a dose 0,3; 0,6; 0,9;1,2; and 1,5 mg/mL, positive control group (K+) used NAC 80 mg/mL, and negative control group (K-) used sterile water. This research using Microtitter Plate Biofilm Assay Method with 4 replication. The absorbance value was analized by using One Way Anova statistical analysis, it showed the significance value p=0,000 (p<0,05). By using linier regression, the MBIC was obtained at the dose of 0,3468 mg/mL. In conclusion, methanolic extract of garlic had ability to inhibit the growth biofilm of P. aeruginosa. Keywords: biofilm, garlic, Minimum Biofilm Inhibitory Concentration, P. aeruginosa